2017
DOI: 10.18632/oncotarget.17695
|View full text |Cite
|
Sign up to set email alerts
|

Novel PPARα agonist MHY553 alleviates hepatic steatosis by increasing fatty acid oxidation and decreasing inflammation during aging

Abstract: Hepatic steatosis is frequently observed in obese and aged individuals. Because hepatic steatosis is closely associated with metabolic syndromes, including insulin resistance, dyslipidemia, and inflammation, numerous efforts have been made to develop compounds that ameliorate it. Here, a novel peroxisome proliferator-activated receptor (PPAR) α agonist, 4-(benzo[d]thiazol-2-yl)benzene-1,3-diol (MHY553) was developed, and investigated its beneficial effects on hepatic steatosis using young and old Sprague-Dawle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Excessive intake of dietary lipids was shown to decrease hepatic PPAR␣ and PGC-1␣ expression with a reduced numerical density of hepatic mitochondria (65). A number of PPAR␣ agonists have been shown to enhance hepatic mitochondrial biogenesis and increase fatty acid ␤-oxidation in diet-induced obese mice (66,67). As an upstream regulator of AKT, PPAR␣, and PGC-1␣, PRMT5 might be a valuable target to treat fatty liver via multiple mechanisms or may be even more broadly applied to other diseases that are associated with mitochondrial dysfunction.…”
Section: Prmt5 Inhibition Enhances Mitochondrial Biogenesismentioning
confidence: 99%
“…Excessive intake of dietary lipids was shown to decrease hepatic PPAR␣ and PGC-1␣ expression with a reduced numerical density of hepatic mitochondria (65). A number of PPAR␣ agonists have been shown to enhance hepatic mitochondrial biogenesis and increase fatty acid ␤-oxidation in diet-induced obese mice (66,67). As an upstream regulator of AKT, PPAR␣, and PGC-1␣, PRMT5 might be a valuable target to treat fatty liver via multiple mechanisms or may be even more broadly applied to other diseases that are associated with mitochondrial dysfunction.…”
Section: Prmt5 Inhibition Enhances Mitochondrial Biogenesismentioning
confidence: 99%
“…25,26 Moreover, it is an appropriate tool of investigation to determine the alteration of fatty acid oxidation [27][28][29] and mitochondrial dysfunction. As known, HepG2 cells represent, among hepatoma cell lines, the most common in vitro model to evaluate DILI and drug metabolism with high similarity to primary human hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a similar dose of elafibranor has previously been shown to reduce steatohepatitis and liver fibrosis following 7 weeks of treatment to MCD diet-fed db/db mice [ 67 ], and other PPAR agonists can reduce fibrotic NASH when administered for 10–12 weeks in mouse and rat CDAA models [ 23 , 71 ]. Previous studies have reported anti-steatotic, anti-inflammatory, and anti-fibrotic effects of PPAR subtype-selective agonists for the α [ 72 , 73 ], δ [ 74 , 75 ], and γ [ 76 , 77 ] isoforms, making it conceivable that elafibranor, a dual PPAR-α/δ agonist, exerts its therapeutic effects through various PPAR-associated signaling mechanisms.…”
Section: Discussionmentioning
confidence: 99%